The Longitudinal Relationship Between eHealth Literacy, Health-Promoting Lifestyles, and Health-Related Quality of Life Among College Students: A Cross-Lagged Analysis - Li, Shaojie; Cui, Guanghui; Zhou, Feixiang; Liu, Siyue; Guo, Yicong; Yin, Yongtian; Xu, Huilan (Frontiers in Public Health, 2022)
Objectives: This study aimed to explore longitudinal associations between eHealth literacy, health-promoting lifestyles, and health-related quality of life (HRQoL) in college students. Methods: From December 2019 (T1) to December 2020 (T2), we administered the eHealth literacy scale, Short-Form Health Survey (SF-12), and Short-Form Health-Promoting Lifestyle Profile Scale to 1181 college students in Jinan, who were recruited for 12 months for the two-stage survey. Results: eHealth literacy, health-promoting lifestyles, and HRQoL had stable positive correlations across time. Cross-lagged analysis showed that eHealth literacy at T1 predicted health-promoting lifestyles at T2 (β=0.080, P=0.006); however, health-promoting lifestyles at T1 did not predict eHealth literacy at T2 (β=-0.026, P=0.499). HRQoL at T1 predicted health-promoting lifestyles at T2 (β=0.147, P<0.001); similar to the eHealth literacy finding, health-promoting lifestyles at T1 did not predict HRQoL at T2 (β=0.045, P=0.142). In addition, eHealth literacy was bi-directionally associated with HRQoL, and the prediction effect of eHealth literacy at T1 to HRQoL at T2 (β=0.078, P=0.008) was slightly higher than the prediction effect of HRQoL at T1 to eHealth literacy at T2 (β=0.074, P=0.023). Conclusion: eHealth literacy and HRQoL were the antecedent variables of college students’ health-promoting lifestyles. There were significant bidirectional relationships between eHealth literacy and HRQoL.